CHARACTERISTICS OF ENTREPRENEURS IN THE PERSPECTIVE OF ISLAMIC NUSANTARA - Oktaviana, Ulfi Kartika; Supriyanto, Achmad Sani; Siswanto, Siswanto; Al Idrus, Salim (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
Islam Nusantara refers to the relationship between Islam and Indonesian culture. Entrepreneurs are inextricably linked to the roots of local culture and community wisdom. Local culture has a big impact on an Islamic entrepreneur's mindset and level of success. This article demonstrates Islam Nusantara's spirit of entrepreneurship. Islam Nusantara's primary character is Islam, however these figures also stand for friendship, harmony, and peace. Attitudes such as respect, appreciation, optimism, and generosity toward others are reflections of this calm character. Harmony, the second component, calls for a mentality capable of balancing two opposing viewpoints. According to the hadith and Qur'anic teachings of muamalah, the third character, Sillahturrahmi, rewards good social interaction. The three attributes of Islam Nusantara align with the essence of entrepreneurship and have the potential to enhance its essence.